International finance : theory into practice - Sercu, Piet. (Princeton : Princeton University Press, 2009)
International Finance presents the corporate uses of international financial markets to upper undergraduate and graduate students of business finance and financial economics. Combining practical knowledge, up-to-date theories, and real-world applications, this textbook explores issues of valuation, funding, and risk management. International Finance shows how theoretical applications can be brought into managerial practice. The text includes an extensive introduction followed by three main sections: currency markets; exchange risk, exposure, and risk management; and long-term international funding and direct investment. Each section begins with a short case study, and each of the sections' chapters concludes with a CFO summary, examining how a hypothetical chief financial officer might apply topics to a managerial setting.
Includes bibliographical references (p. [801]-811) and index.
rpm 15/05/13
Loans
Keywords: International finance; International Funding